Influence Of Aviation And Biofuel Absoprtion On The Mechanical And Post-Fire Mechanical Properties Of Gfrp Composites - Kumarasamy, Sharmendran (2019)
The degradation of the mechanical room temperature and post-fire properties of Glass Fibre Reinforced Polymer (GFRP) composite due to fuel attack has been experimentally investigated. Three types of aviation fuel were used to environmentally age the GFRP specimens using an immersion bath technique. The fuels used are aviation fuels, an alternative fuel which was palm oil-based biodiesel and a blended fuel mixture consist of 80% kerosene and 20% biodiesel based on volume ratio. The GFRP were manufactured using vacuum assisted resin transfer moulding (VARTM) to obtain a high quality composite. All of the sorption behaviours obtained display a classic Fickian sorption curve. Tensile and compression test were conducted on the immersed specimens after being immersed for 15 hours0.5 to study the influence of the fuel on the mechanical properties of the GFRP laminates. A slight decrement in the mechanical properties of the immersed specimens compared to the standard specimens was observed. However, the specimen retained most of its strength with on an overall reduction of less than 6% for tensile stress, 18% for tensile modulus, 12% for compressive stress and 14% for compressive modulus. In this research, the post-fire mechanical properties of the immersed GFRP laminates were also investigated. The post-fire experiment data shows that increasing the exposure time toward the heat will further decrease the mechanical properties. For an exposure of 60 seconds for standard specimens and 70 seconds for immersed specimens, all of the specimens retained most of their mechanical properties.Keywords-component; GFRP; mechanical properties; aviation fuel; alternative fuel; blended fuel; post-fire properties.